Application of the correct design of successive self-nucleation and annealing (SSA) to study the stereo-defects and its distribution of homo- and co-polypropylene. Issue 40 (9th May 2017) - Ding, Cong; Zhang, Geng; Gu, Jiangjiang; Cao, Feifei; Zheng, Xinsheng
Abstract : The SSA revealed the differences in molecular chain microstructure of different PP samples when the preliminary characterization found that the homo-polypropylene or co-polypropylene samples had the similar mechanical and thermal properties. Abstract : The stereo-defects and its distribution of four homo- and co-polypropylene samples with different processing properties were studied through the correct design Successive Self-Nucleation and Annealing (SSA), and other characterization methods such as Differential Scanning Calorimetry (DSC), Gel Permeation Chromatography (GPC), Temperature Rising Elution Fractionation (TREF), respectively. Firstly, the preliminary characterization found that the two homo-polypropylene or co-polypropylene samples had the similar mechanical and thermal properties, and the SSA results also revealed the internal microstructure of the different kind of polypropylene was almost exactly the same, representing the alike isotactic sequence length, the fractions weight of the isotactic sequence, and the isotactic sequence length distribution of the same kind of polypropylene. Compared with the homo-polypropylene, the DSC, GPC, and TREF tests indicated there were difference in the properties of the co-polypropylene samples, revealing the disparities in molecular chain microstructure. The SSA results after the correct T s for each sample showed there were obvious differences in the (statistical) lamellar thickness and its distribution and the fractions weight of different fractions after SSA treatment, further revealing the microstructure difference on the isotactic sequence length, and the isotactic sequence length distribution of homo- and co-polypropylene samples. Besides, the correct design SSA also indicated the polar copolymer monomer had a great influence on the high isotactic component in co-polypropylene microstructure.